The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5761/atcs.oa.13-00155
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative 18F-Fluorodeoxyglucose Positron Emission Tomography can Predict the Tumor Malignancy of Small Peripheral Lung Cancer

Abstract: Purpose: Recent advances in image diagnostic technology have enhanced the discovery of peripheral small size lung cancers. Here, we examined the utility of 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) for the evaluation of grade of tumor malignant potency. Methods: Seventy-nine patients with peripheral small lung cancers (≤2 cm) who underwent surgical resections and preoperative FDG-PET were enrolled. The correlations between the maximum standardized uptake value (SUV max ) and various clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…The present study demonstrated that the prognoses of patients with cN1 NSCLC were associated with age, the CEA value, and the primary tumor’s SUVmax value. The primary tumor’s SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports regarding the associations between FDG uptake and tumor malignancy [ 13 16 ]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation [ 17 – 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that the prognoses of patients with cN1 NSCLC were associated with age, the CEA value, and the primary tumor’s SUVmax value. The primary tumor’s SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports regarding the associations between FDG uptake and tumor malignancy [ 13 16 ]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation [ 17 – 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…SUVmax value was also an independent prognostic factor for both OS and RFS, which is consistent with previous reports on the associations between FDG uptake and tumor malignancy [13][14][15][16]. Clinical and experimental studies have indicated that FDG accumulation during PET examination was correlated with tumor growth rate, cell density, and cell differentiation.…”
supporting
confidence: 91%
“…Many studies have indicated that FDG-PET/CT is useful for determining the c-stage and therapeutic strategy for small-size lung cancer. [4][5][6][7][8] However, a recent study in the Netherlands reported that the accuracy of the c-stage for non-small-cell lung cancer (NSCLC) was low, even in the era of FDG-PET/CT. 9,10 Few studies have investigated whether the PET/CT findings can salvage the discordance between the clinical and pathologic TNM staging.…”
Section: Introductionmentioning
confidence: 99%